Construction Productivity in the Multilayer Subcontracting System The Case of Singapore - Sui Pheng, Low.; Jia Zheng, Sim.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book focuses on current subcontracting practices in the construction industry and their effects on Singapore's construction productivity. It offers readers a better understanding of how the fragmentation of large and small firms in Singapore impacts construction productivity when operating under the commonly adopted multilayer subcontracting system (MLSS), which extends globally to the construction industries in other countries that have adopted the MLSS. The book also assesses the effectiveness of subcontracting practices in helping local contractors improve their construction productivity (and thereby improve the industry's overall productivity). In closing, it provides recommendations on how the problems associated with the MLSS can best be addressed, and how its benefits can be capitalized on through organizational learning. .
Introduction -- Nature of the Construction Industry -- Case of Singapore's Construction Industry -- Theoretical Review for Singapore's Subcontracting Practices -- Research Design and Methodology -- Research Findings -- Analysis of Research Findings -- Interview Findings -- Conclusion.
Keywords: Construction industry -- Management; Project management; Industrial Management; Construction Management; Project Management; Industrial Management